Perda Bernuansa Syariah Dan Hubungannya Dengan Konstitusi - Muhammad Alim (Jurnal Hukum IUS QUIA IUSTUM, 2010)
Legal history found that the practice of judicial review has been long recognized in the Muslim community starting the period of the propthet Muhammad Rasullah Saw hundreds years ago long before Justice John Marshall of the United States of America’s Supreme Court in 1803 made a decision for a constitutional case ‘writ of mandamus’ filed by Marbury. The US Supreme Court declared the Judiciary Act 1789 was against the Article II Section of 2 of the US Constitution. The propthe Muhammad saw was remined by Allah SWT for his statement that over the prophtet ojection to use honey as medicine was against the holly Quran. The holly Quran is the hightest-ranked sources of law in Islam. In term of the Perda Syariah should be no objection as long it is line with the holy Quran and no doubt the Perda should also considered in line with the 1945 ConstituionKey words : Islamic law created by local government